2021
DOI: 10.1136/emermed-2020-210409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on emergency medical service response to out-of-hospital cardiac arrests in Taiwan: a retrospective observational study

Abstract: BackgroundEmergency medical service (EMS) personnel have high COVID-19 risk during resuscitation. The resuscitation protocol for patients with out-of-hospital cardiac arrest (OHCA) was modified in response to the COVID-19 pandemic. However, how the adjustments in the EMS system affected patients with OHCA remains unclear.MethodsWe analysed data from the Taichung OHCA registry system. We compared OHCA outcomes and rescue records for 622 cases during the COVID-19 outbreak period (1 February to 30 April 2020) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 25 publications
(24 reference statements)
4
40
3
Order By: Relevance
“…A flow diagram showing stages of database search and study selection is shown in Figure 1. Twenty-seven studies reported OHCA outcomes in pre-vs. intra-COVID-19 periods [23,24,[26][27][28][29]31,33,35,[37][38][39][40][41][42][44][45][46][47][48][49][50][51][52][53], and OHCA outcomes in SARS-CoV-2-positive vs. -negative patients were reported in seven trials [25,30,32,34,36,43,51]. Characteristics of the individual studies are presented in Tables S1 and S2.…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations
“…A flow diagram showing stages of database search and study selection is shown in Figure 1. Twenty-seven studies reported OHCA outcomes in pre-vs. intra-COVID-19 periods [23,24,[26][27][28][29]31,33,35,[37][38][39][40][41][42][44][45][46][47][48][49][50][51][52][53], and OHCA outcomes in SARS-CoV-2-positive vs. -negative patients were reported in seven trials [25,30,32,34,36,43,51]. Characteristics of the individual studies are presented in Tables S1 and S2.…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
“…The Cochrane risk of bias of the included studies is shown in Figures S1 and S2. The overall risk of bias was judged as low in twenty-nine studies [23][24][25][26][27][28][29][30][31][32][34][35][36][37][38][39][40][41][42][43][44][45][46][48][49][50][51][52][53], and reviewers indicate some concerns on the other two [33,47].…”
Section: Characteristics Of Studies Included In the Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a centralized public EMS system may improve coordination between different stakeholders during the COVID-19 pandemic and reduce OHCA mortality rates. [50,51] However, more investigation is needed in this eld. Further research is also needed to investigate measures for minimizing COVID-19 transmission during resuscitation, such as supraglottic airway use and mechanical CPR, as well as the barriers to implementing them during the pandemic.…”
Section: Discussionmentioning
confidence: 99%